Thickness Dependence of Optical Properties of Amorphous Indium Gallium Zinc Oxide Thin Films: Effects of Free-Electrons and Quantum Confinement. (22nd January 2015) - Li, X. D.; Chen, Siyuan; Chen, T. P.; Liu, Y.
Abstract : Dielectric function of amorphous indium gallium zinc oxide (a-IGZO) thin films is found to shift significantly with the film thickness, which is attributed to the changes in both the bandgap and electron concentration of the IGZO thin films with the film thickness. The ultrathin films (film thickness < ∼20 nm) exhibit a bandgap expansion with reducing film thickness due to the quantum confinement effect; while the thicker films (thickness > ∼35 nm) demonstrate the free-electron effect, i.e. the Burstein-Moss shift and increase of free-electrons absorption with increasing electron concentration